Positive innovative thinking based on the integration of spiritual knowledge through the subjects of design and technology - Zaipah, Ismail; Aede Hatib, Musta’amal @ Jamal; Nornazira, Suhairom; Rohana, Hamzah (Human Resource Management Academic Research Society, 2024)
Today's education system places great importance on student achievement, especially in terms of innovative and creative abilities, along with the student's personal and personality development. However, the era of globalization and digitalization also pushes students toward negative innovation. The increase in negative innovative activities carried out by a few students has become a hot conversation in the community in the mass media. Therefore, improving students' positive innovative thinking is urgently needed. The subject of Design and Technology (RBT) is a subject that gives students early exposure to innovative and creative aspects to produce useful products. However, the teaching and learning process and the existing curriculum often ignore the spiritual element, which can play an important role in forming positive innovative thinking and student morals. This research is in line with the Sustainable Development Goals (SDG), especially SDG 4 (Quality Education) and SDG 9 (Industry, Innovation, and Infrastructure), by emphasizing the integration of intellectual and spiritual knowledge education to produce students with positive innovative thinking and noble character. This concept paper aims to discuss the importance of the integration of intellectual and spiritual knowledge in the subject of Design and Technology to increase the positive innovative thinking of students. This study is a qualitative study using the bibliographic highlight method by referencing material from scientific sources of books, articles, and proceedings papers to get a clearer picture of the issue under study. The research results show that the approach of integrating intellectual and spiritual knowledge is very important to give birth to people who are balanced in intellectual, physical, emotional, and spiritual aspects. This balance is the basis for being an individual who is responsible for oneself, society, and the environment. Therefore, the approach of knowledge integration needs to be implemented in the subjects of Design and Technology to produce students who have positive innovative thinking to create quality products and benefit the community. This study shows the teaching and learning process by combining spiritual elements in the subjects of Design and Technology. It is very important to form positive innovative thinking of students. This research contributes to the existing literature by providing empirical evidence of the benefits of such integration processes, thereby guiding educators to produce a more holistic education.